2019
DOI: 10.3390/cancers11101472
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives in Cancer Immunotherapy

Abstract: Different immunotherapeutic approaches have proved to be of significant clinical value to many patients with different types of advanced cancer. However, we need more precise immunotherapies and predictive biomarkers to increase the successful response rates. The advent of next generation sequencing technologies and their applications in immuno-oncology has helped us tremendously towards this aim. We are now moving towards the realization of personalized medicine, thus, significantly increasing our expectation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
121
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(134 citation statements)
references
References 377 publications
0
121
0
1
Order By: Relevance
“…In this scenario, several species have been strongly correlated with oral carcinoma, such as Capnocytophaga gingivalis, Fusobacterium sp., Streptococcus sp., Peptostreptococcus sp., Porphyromonas gingivalis and Prevotella sp., due to the fact that these bacteria may promote inflammation, cell proliferation and the production of some oncogenic substances (90). Recent findings have shown that the evaluation of oral microbiota and microbiome may provide important information on oral cancer oncogenesis, outcome prediction and therapeutic response (including immunotherapy) (198,199). In addition, thanks to the new high-throughput molecular technologies it was possible to define the precise composition and gene expression (micro-biome) of oral bacteria in OSCC patients and normal controls identifying specific strains associated with an increased risk of OSCC development (1,200).…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, several species have been strongly correlated with oral carcinoma, such as Capnocytophaga gingivalis, Fusobacterium sp., Streptococcus sp., Peptostreptococcus sp., Porphyromonas gingivalis and Prevotella sp., due to the fact that these bacteria may promote inflammation, cell proliferation and the production of some oncogenic substances (90). Recent findings have shown that the evaluation of oral microbiota and microbiome may provide important information on oral cancer oncogenesis, outcome prediction and therapeutic response (including immunotherapy) (198,199). In addition, thanks to the new high-throughput molecular technologies it was possible to define the precise composition and gene expression (micro-biome) of oral bacteria in OSCC patients and normal controls identifying specific strains associated with an increased risk of OSCC development (1,200).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, different immunotherapeutic approaches have proved to be successful in treating many malignant cancers (Del Paggio, 2018). These include immune checkpoint blockade, cytokine therapy, cellular therapy, and therapeutic vaccines (Christofi et al, 2019). Immune checkpoint inhibitors such as cytotoxic T lymphocyte antigen-4 (CTLA-4), programmed cell death protein 1 (PD-1), and PD-1 ligand (PD-L1) antibodies have shown significant antitumor activity in several human cancers (Le et al, 2015a;Reck et al, 2016;Wolchok et al, 2013) .…”
Section: Introductionmentioning
confidence: 99%
“…Preventative and therapeutic vaccines are also effective in several cancers, such as human papillomavirus (Mammas et al, 2011), hepatitis B virus vaccines (Chemin, 2010), Sipuleucel-T, and GVAX vaccine against prostate cancer (Kantoff et al, 2010;Le et al, 2015b). However, there is disparity in response rates across and within tumor types, and not all patients benefit from immunotherapy (Christofi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer immunotherapy based on blockade of the programmed cell death protein 1 (PD-1)/PD-1 ligand 1 (PD-L1) pathway with monoclonal antibodies is increasingly applied in clinical practice [1][2][3][4]. Initially, pembrolizumab and nivolumab were approved by the Food and Drug Administration (FDA) in 2014 for the treatment of patients with advanced melanomas [4].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, pembrolizumab and nivolumab were approved by the Food and Drug Administration (FDA) in 2014 for the treatment of patients with advanced melanomas [4]. The number of approved antibodies for the blockade of PD-1/PD-L1 signaling has rapidly increased and improved the therapy of different malignant diseases in patients unsuccessfully treated by other methods [1]. Thus far, six antibodies (pembrolizumab, nivolumab, atezolizumab, durvalumab, avelumab, and cemiplimab) have been approved by the FDA [5,6].…”
Section: Introductionmentioning
confidence: 99%